(untitled) (Mustansiria Dental Journal, 2018)
The aims of this study were to investigate the degree of visibility of maxillary and mandibular anterior teeth surfaces when the lips are at rest. And to evaluated its correlation with age and sex. As well as to determine the correlation of the upper lip length with the amount of clinical free way space. Two hundred adults (100 males and 100 females) were examined. All the subjects had maxillary and mandibular anterior teeth present with bilateral molar support. The measurement was taken at the midpoint of the each anterior tooth when the lips and lower jaw were at rest position. The length of upper lip was measured from the base of the columella to the tip of the philtrum at the midline of the face. Artificial landmarks (adhesive tape) were placed on the more prominent parts of the nose and chin of each subject. The clinical free way space value was obtained by subtracting measured vertical dimension of occlusion from postural vertical dimension. Females showed more of the maxillary central and lateral incisors than males. With increasing age, the amount of maxillary anterior teeth that was visible at rest position decreased. Statistically the amount of visible surface of maxillary central incisor showed significant differences with increasing age of subjects. The subjects with shorter upper lips displayed more of maxillary central and lateral incisors than those with longer upper lips. Significant differences were founded between the visible amount of maxillary central and lateral incisors and lip length. It was founded that the more increased in the length of upper lip, the more decreased in the vertical dimension as increased in the amount of clinical free way space which is founded within the recommended range (2-4mm). High significant differences were founded between the amount of clinical free way space and length of upper lip. Females showed shorter upper lip than males and high significant differences were founded between sexes and upper lip length.